(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The article analyzes how the development of fintech companies and the digitalization of the financial sector affect the structure and dynamics of monetary circulation, including the transformation of cash demand, changes in the velocity of money, and the evolution of payment infrastructure. It is shown that the spread of digital payment services and fintech ecosystems increases the share of cashless payments, enhances the transparency of monetary flows, and transforms monetary transmission channels. It is argued that the stability of monetary circulation under fintech expansion depends on the quality of digital platform regulation, the reliability of payment infrastructure, and the consistency of financial digitalization with the goals of the central bank’s monetary policy.